Variabel Yang Mempengaruhi Penggunaan Bank Digital Melalui Behavioral Intention - Widjaja, Kevin; Nurjanah, Siti (Research and Community Service UNIVERSITAS KALBIS, 2025)
This research aims to determine the factors that influence a person's use of Digital Banks. The indicators used in this research are Perceived Ease of Use (POEU), Performance Expectancy (PE), Facilitating Condition (FC), Behavioural Intention (BI) as an intervening variable, and Use Intention (UI). This research uses a quantitative research approach using data collection methods by filling out online questionnaires from 150 sources who have used Digital Bank. Using the SEM (Structural Equation Mode) analysis method produces a test that Performance Expectancy, Facilitating Conditions have a direct and indirect influence on Use Intention, however perceived Ease of Use does not have a direct or indirect influence by showing a value of -2.550 and -0.657 in the model analysis testing that has been carried out. This negative value shows that the Perceived Ease of Use variable does not influence using Digital Bank. In utilizing digital banking services, a person's habits can be directly and significantly influenced by performance expectations.